J/ψ, Y and B meson production in proton–proton collisions at the LHC - Kotlyar, V.V.; Krupina, N.V. (Вопросы атомной науки и техники, 2012)
Mechanisms of J/ψ, Υ and B meson production in proton-proton scattering at total energy 7 TeV are studied with the help of event generator Pythia 8. Uncertainties in the total and differential cross sections due to choice of the renormalization and factorization scales are analyzed for prompt J/ψ and Υ production. Sensitivity of the inclusive cross sections on contributions of J/ψ from decay of b–hadrons is also discussed. Results of the calculations are compared with the ALICE, ATLAS, CMS, and LHCb data in order to assess potentialities and validity of the approaches, in particular color singlet and octet models, used in the simulations. Механизмы рождения J/ψ-,Υ- и B-мезонов в рассеянии протонов с полной энергией 7 ТэВ изучаются с помощью генератора событий Пифия 8. Неопределённости в значениях полных и дифференциальных сечений реакций, которые обусловлены выбором шкал перенормировки и факторизации, анализируются для рождения мгновенных J/ψ и Υ-мезонов. Исследуется также чувствительность инклюзивных сечений реакции к вкладам J/ψ источником которых являются распады b–адронов. Для проверки моделей, используемых в моделировании рассмотренных процессов, результаты расчётов сравниваются с данными, полученными коллаборациями ALICE, ATLAS, CMS и LHCb. Механізми народження J/ψ-, Υ- та B-мезонів у розсіянні протонів з повною енергією 7 ТеВ вивчаються за допомогою генератора подій Піфія 8. Невизначеність повних та диференційних перерізів реакцій, що зумовлена вибором шкал перенормування та факторизації, аналізується для народження миттєвих J/ψ- та Υ-мезонів. Досліджується також чутливість інклюзивних перерізів реакцій до внесків J/ψ джерелом яких є розпад b–адронів. Для перевірки моделей, що використовуються в моделюванні розглянутих процесів, результати розрахунків порівнюються з даними, що було отримано колабораціями ALICE, ATLAS, CMS та LHCb.